Study on Intention to Using Digital Banking Study: Bank Jago - Kasmo, Arief Bowo Prayoga; Khahfi, Aqmal Muhammad; Oteino, Ojatta Dominic (Journal of Indonesia Marketing Association (IMA), 2024)
The growth of digital bank users in Indonesia is quite high compared to other countries in Asia, however, in Indonesia the percentage of digital bank users is still below that of traditional bank users. Bank Jago is the digital bank with the highest user growth among digital banks in Indonesia. The objective of this research is to examine the influence of Perceived Ease, Efficiency, and Trust on the Interest in Using Bank Jago as a Digital Bank. The sample selection technique uses purposive sampling with a predetermined sample size of 170 respondents. Data analysis techniques include quantitative descriptive analysis and structural equation modeling. The analyzed equation model includes the outer model, inner model, and hypothesis testing. Based on the results obtained using PLS-SEM software version 3.0, it is found that there is a significant positive influence between the perceived ease, the efficiency, and trust on the interest in using Bank Jago as a digital bank. There are three suggestions according to the results of this study, one of which is to increase the trust of potential customers, digital banks are expected to evaluate the digital-savvy generation by being active in social media and digital platforms to communicate with the digital-savvy generation and other audiences to assist in marketing, service, and stakeholder engagement.